Re-thinking the implementation of punishment of Shariah offences in Malaysia - Wan Muhammad, Ramizah (2017)
Punishment under the criminal law is often associated with mental and physical restraint in the form of imprisonment and whipping. In the pursuit of punishing the offender, the Society often neglect the needs to rehabilitate and educate the offender. Community service as form of non-custodial offence can be the alternative to the conventional punishment as it can help the offender to return to the society’s fold. The element of contributing to the society is the important point that separates community service from other type of punishment. One of the characteristics of Islamic penal system is the possibility of repentance. Community service can be one of the evidence to support the fact that the offender had repented. Shariah court in Malaysia should adopt community service as one of the alternative punishments.